Operationalising a large research programme tackling complex urban and planetary health problems: a case study approach to critical reflection - Daniel Black; Geoff Bates; Sarah Ayres; Krista Bondy; Rosalie Callway; Neil Carhart; John Coggon; Andy Gibson; Alistair Hunt; Ges Rosenberg (Sustainability Science, 2023)
Addressing increasingly urgent global challenges requires the rapid mobilisation of new research groups that are large in scale, co-produced and focussed explicitly on investigating root causes at a systemic level. This requires new ways of operationalising and funding research programmes to better support effective interdisciplinary and transdisciplinary (ID/TD) partnerships between a wide range of academic disciplines and stakeholder groups. Understanding the challenges and approaches that teams can follow to overcome them can come through critical reflection on experiences initiating new research programmes of this nature and sharing of these reflections. We aimed to offer a framework for critical reflection and an overview of how we developed it and to share our reflections on operationalising a newly formed large-scale ID/TD research programme. We present a framework of 10 areas for critical reflection: systems, unknowns and imperfection, ID/TD understanding, values, societal impact, context and stakeholder knowledge, project understanding and direction, team cohesion, decision-making, communications and method development. We reflect on our experience of operationalising the research programme in these areas. Based on this critical examination of our experiences and the processes we adopted, we make recommendations for teams seeking to tackle important and highly complex global challenges, and for those who fund or support such research groups. Our reflections point to an overarching challenge of the structural and institutional barriers to cross-disciplinary research of this nature.